Renin‐Angiotensin‐Aldosterone System Blockers in Elderly Adults with Chronic Kidney Disease without Diabetes Mellitus or Proteinuria. Issue 12 (December 2015) - Arora, Pradeep; Golzy, Mojgan; Patel, Nilang; Quigg, Richard; Carter, Randolph L.; Lohr, James W.
Abstract : Objectives: To compare the effect of renin‐angiotensin‐aldosterone system (RAAS) blockers with that of other antihypertensive agents on outcomes in a cohort of elderly veterans with incident chronic kidney disease (CKD) without diabetes mellitus or proteinuria. Design: Retrospective cohort study. Setting: Veterans Affairs (VA) Upstate New York Healthcare System. Participants: All participants were seen in primary care clinic in Veterans Integrated Service Network 2, which comprises five VA medical centers and 29 community‐based outpatient clinics, from April 2001 to April 2008. Veterans with incident CKD who were taking antihypertensive medications and did not have proteinuria or diabetes mellitus on the date of onset of CKD were selected from this population. Measurements: The outcome variables studied were progression of kidney disease (doubling of serum creatinine level or Stage 5 CKD (estimated glomerular filtration rate <15 mL/min per 1.73 m 2 )), all‐cause mortality, and combined outcome. Results: Analysis included 2, 474 participants, 47.9% of whom were taking RAAS blockers at baseline and the rest other antihypertensives. Time‐varying Cox proportional hazards analyses did not reveal a statistically significant difference in primary combined outcome in participants taking RAAS blockers and those taking other antihypertensives (hazard ratio = 1.09, 95% confidence interval = 0.93–1.27). There was also no significant effect on individual outcomes (death or progression of kidney disease). Conclusion: Use of RAAS blockers was not associated with less hazard of combined and individual outcomes (doubling of serum creatinine, Stage 5 CKD, death) in elderly veterans with incident CKD without diabetes mellitus or proteinuria.